Blue food proteins: Novel extraction technologies, properties, bioactivities and applications in foods - Shuo Fan; Yaxin Yin; Qirui Liu; Xinru Yang; Daodong Pan; Zhen Wu; Ming Du; Maolin Tu (Current Research in Food Science)
With the growing demand for healthy and sustainable food, blue food proteins have emerged as an important way to address resource-intensive production and environmental concerns. This paper systematically reviewed the extraction technologies, properties and bioactivities of blue food proteins and explored their wide range of applications. The novel extraction technologies not only improve the extraction efficiency of the proteins, shorten the production time and have environmental advantages, but also enhance the protein properties and facilitate subsequent applications. The amino acid composition of the blue food proteins is close to the FAO recommended standard and better than most of the livestock proteins, with excellent solubility and water holding capacity. Some of the proteins also have significant bioactivity and show great potential for improving health. Applications include emulsions, protein films, microcapsules, food colorants, dietary supplements, 3D printing materials, and cultured meat. This paper provides theoretical support for further research and application of blue food proteins and promotes their wider application in future food products.